2020
DOI: 10.1016/j.jaci.2020.03.004
|View full text |Cite
|
Sign up to set email alerts
|

RGS4 promotes allergen- and aspirin-associated airway hyperresponsiveness by inhibiting PGE2 biosynthesis

Abstract: Background: Allergens elicit host production of mediators acting on G-protein-coupled receptors to regulate airway tone. Among these is prostaglandin E2 (PGE2), which, in addition to its role as a bronchodilator, has anti-inflammatory actions. Some patients with asthma develop bronchospasm after the ingestion of aspirin and other nonsteroidal anti-inflammatory

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 56 publications
1
4
0
Order By: Relevance
“…Expression of genes associated with the ECM formation was significantly downregulated in IL-31RA −/− mice treated with bleomycin when compared to wildtype mice. Notably, genes associated with epithelial tissue integrity ( Krt5 and Krt14 ), protein Gα signaling, as well as previously reported genes associated with lung function and remodeling ( Arg1, Ccl28 and Rgs4 ) were down regulated in IL-31RA −/− fibrotic mice ( 50 52 ). Weathington et al ( 53 ) have recently reported an association between increased expression of the genes KCNJ2 and Krt18 in the setting of asthma, suggesting a strong relationship between lung function and tissue remodeling.…”
Section: Discussionsupporting
confidence: 75%
“…Expression of genes associated with the ECM formation was significantly downregulated in IL-31RA −/− mice treated with bleomycin when compared to wildtype mice. Notably, genes associated with epithelial tissue integrity ( Krt5 and Krt14 ), protein Gα signaling, as well as previously reported genes associated with lung function and remodeling ( Arg1, Ccl28 and Rgs4 ) were down regulated in IL-31RA −/− fibrotic mice ( 50 52 ). Weathington et al ( 53 ) have recently reported an association between increased expression of the genes KCNJ2 and Krt18 in the setting of asthma, suggesting a strong relationship between lung function and tissue remodeling.…”
Section: Discussionsupporting
confidence: 75%
“…RGS4 was found to be upregulated too. However, previous studies have shown that RGS4 promotes allergen- and aspirin-induced airway hyperresponsiveness [ 25 ]. Using Gene Ontology (GO) enrichment analysis, we determined that the differentially expressed mRNAs were associated with processes commonly associated with inflammation, such as immune responses, cytokines and their receptor signalling pathways, and receptor–ligand activity.…”
Section: Resultsmentioning
confidence: 99%
“…In contrast to RGS5 knockout, RGS2-/-mice displayed increased acute inflammation upon house dust mite and LPS inoculation and an augmented development of pulmonary fibrosis [4,7,24]. Increase of RGS4 in human bronchial smooth muscle cells caused severe airway obstruction and RGS4-/-mice exhibited diminished allergen-induced AHR through the increased secretion of the bronchodilator PGE2 [25,26]. This suggests that the signaling pathways and biological roles of the different RGS proteins may be quite specific.…”
Section: Discussionmentioning
confidence: 99%